Location, management strategy and workers' pensions - Clark, G (Pion Ltd., 1990)
This paper focuses upon the relationships between management strategy, location decisionmaking, and private pension liabilities. Analysis is based upon a recent suit in federal Court brought by past employees of Continental Can Corporation against the corporation, alleging that it had deliberately relocated and restructured production at its Pittsburgh plant so as to illegally avoid early-retirement pension obligations. In narrative form I set out the essential details of the case and document in detail how the corporation reallocated production by plant location and the age and seniority of workers. It is suggested that this kind of locational-restructuring strategy is more common than often supposed and it is argued that corporations' pension obligations have fundamental, but little understood, implications for the process of restructuring American industry.